High School Students' Perceptions of Online Learning During The Covid-19 Pandemic on The Aceh Mountains - Awal Kurnia Putra Nasution; Muhammad Hasyimsyah Batubara; Nurmalina Nurmalina; Imam Munandar (Universitas Muhammadiyah Mataram, 2021)
High school learning changed from traditional (face-to-face) learning to online learning during the Covid-19 pandemic. Students' perceptions of learning are one of the supporting factors for successful learning, including online learning. The purpose of this study was to determine the perceptions of high school students towards online learning during the Covid-19 pandemic and what learning media they like the most. This online survey research will explore high school students' perceptions of online learning that has taken place, for data discussion to answer research problems, a descriptive approach was used.. The research respondents were 592 students from 2 districts in the mountains of Aceh, namely Central Aceh and Bener Meriah. The results showed that high school students gave a poor perception of online learning; the learning media that students liked was the WhatsApp application. Students' loneliness causes this perception. Due to a lack of